Variations in out-of-pocket spending and factors influencing catastrophic health expenditure of households with patients suffering from chronic conditions in four districts in Sri Lanka - Anuji Gamage; Nuwan Darshana; Therani Gunasekara; Deepika Attygalle; S. Sridharan (BMC Health Services Research, 2024)
Abstract Introduction Healthcare financing systems, dependent on out-of-pocket expenditure(OOPE), impose a heavy burden on those who use the services regularly, such as patients suffering from chronic diseases. High OOPE for health services leads to decreased utilization of the services and/or catastrophic health expenditure, which would significantly impede the achievement of Universal Health coverage. Objective We aimed to determine variations in OOPE and factors associated with Catastrophic Health Expenditure (CHE) of households with patients suffering from non-communicable diseases(NCDs) in four districts. Methods A survey was conducted among 2344 adult patients having selected NCD/s. Multi-stage stratified cluster sampling selected respondents from 4 districts representing urban, rural, semi-urban, and estate. Data was collected using a validated interviewer-administered questionnaire. Logistic regression identified the predictors of CHE(> 40%). Significance was considered as 0.05. Results Common NCDs were hypertension(29.1%), diabetes(26.8.0%), hyperlipidaemia(9.8%) and asthma(8.2%). Only 13% reported complications associated with NCDs. Fifty-six percent(N = 1304) were on regular clinic follow-up, and majority utilized western-medical government hospitals(N = 916,70.2%). There were 252 hospital admissions for chronic-disease management in the past 12 months. Majority(86%) were admitted to government sector hospitals. Most patients incurred nearly SLR 3000 per clinic visit and SLR 3300 per hospital admission. CHE was beyond 40% for 13.5% of the hospital admissions and 6.1% of the regular clinic follow-up. Patients admitted to private sector hospitals had 2.61 times higher CHE than those admitted to government sector hospitals. Conclusions Patients with NCDs incurred high OOPE and faced CHE during healthcare seeking in Sri Lanka. The prevalence of NCDs and complications were high among the participants. Patients with chronic conditions incur high OOPE for a single clinic visit and a hospital admission. Patients incur high OOPE on direct medical costs, and district-wise variations were observed. The proportion with more than 40% CHE on monthly clinic care was high. Patients being followed up in the government sector are more likely to have CHE when obtaining healthcare and are more likely to face barriers in obtaining needed health services. The services rendered to patients with chronic conditions warrant a more integrative approach to reduce the burden of costs and related complications.